Captopril in heart failure. A double blind controlled trial. Issue 5 (November 1984) - Cleland, J G; Dargie, H J; Hodsman, G P; Ball, S G; Robertson, J I; Morton, J J; East, B W; Robertson, I; Murray, G D; Gillen, G
Abstract : The effect of the converting enzyme inhibitor captopril as long term treatment was investigated in 14 patients with severe congestive heart failure in a double blind trial. Captopril reduced plasma concentrations of angiotensin II and noradrenaline, with a converse increase in active renin concentration. Effective renal plasma flow increased and renal vascular resistance fell; glomerular filtration rate did not change. Serum urea and creatinine concentrations rose. Both serum and total body potassium contents increased; there were no long term changes in serum concentration or total body content of sodium. Exercise tolerance was appreciably improved, and dyspnoea and fatigue lessened. Left ventricular end systolic and end diastolic dimensions were reduced. There was an appreciable reduction in complex ventricular ectopic rhythms. Adverse effects were few: weight gain and fluid retention were evident in five patients when captopril was introduced and two patients initially experienced mild postural dizziness; rashes in two patients did not recur when the drug was reintroduced at a lower dose; there was a significant reduction in white cell count overall, but the lowest individual white cell count was 4000 X 10(6)/l. Captopril thus seemed to be of considerable value in the long term treatment of severe cardiac failure.